Effect of storage temperature and duration on rheological and thermal characteristics of superolein oleogels - Saw, Mei Huey; Lim, Wen Huei; Yeoh, Chee Beng; Tan, Chin Ping (Malaysian Palm Oil Board, 2023)
The study was conducted to investigate the effects of storage temperature and duration on the rheological and thermal characteristics of superolein oleogels derived from 3% w/w of polyglycerol behenic acid ester (PBA), 3% w/w of sunflower wax (SFW) and 8% w/w of fully hydrogenated palm-based monoacylglycerols (MGHO). The results indicated that the storage modulus (G’), loss modulus (G”) and critical stress values were much higher for all the oleogels when stored at 5°C. At 15°C, the rheological parameters for SFW and MGHO oleogels were gradually increased during storage. From the thermal analysis, the peak intensity at approximately 20°C also gradually increased during storage, demonstrating the marked increase in the rheological parameters were due to the crystallisation of the triacylglycerol (TAG) in the superolein during the three-day storage. This effect was not observed for PBA oleogels, showing that the PBA inhibited or delayed crystallisation of the superolein molecules at 15°C. However, an extended storage study revealed that the PBA actually delayed and did not inhibit the crystallisation of the superolein. At 25°C, all the oleogels were highly unstable with poor thermal and rheological properties. The results suggested that 15°C was a more suitable temperature for the storage of superolein oleogels.